miR-193a-3p interaction with HMGB1 downregulates human endothelial cell proliferation and migration - Khoo, C; Roubelakis, M; Schrader, J; Tsaknakis, G; Konietzny, R; Kessler, B; Harris, A; Watt, S (Nature Publishing Group, 2017)
Circulating endothelial colony forming cells (ECFCs) contribute to vascular repair where they are a target for therapy. Since ECFC proliferative potential is increased in cord versus peripheral blood and to define regulatory factors controlling this proliferation, we compared the miRNA profiles of cord blood and peripheral blood ECFC-derived cells. Of the top 25 differentially regulated miRNAs selected, 22 were more highly expressed in peripheral blood ECFC-derived cells. After validating candidate miRNAs by q-RT-PCR, we selected miR-193a-3p for further investigation. The miR-193a-3p mimic reduced cord blood ECFC-derived cell proliferation, migration and vascular tubule formation, while the miR-193a-3p inhibitor significantly enhanced these parameters in peripheral blood ECFC-derived cells. Using in silico miRNA target database analyses combined with proteome arrays and luciferase reporter assays of miR- 193a-3p mimic treated cord blood ECFC-derived cells, we identified 2 novel miR-193a-3p targets, the high mobility group box-1 (HMGB1) and the hypoxia upregulated-1 (HYOU1) gene products. HMGB1 silencing in cord blood ECFC-derived cells confirmed its role in regulating vascular function. Thus, we show, for the first time, that miR-193a-3p negatively regulates human ECFC vasculo/angiogenesis and propose that antagonising miR-193a-3p in less proliferative and less angiogenic ECFC-derived cells will enhance their vasculo/angiogenic function.